(untitled) (Research, Society and Development, 2020)
The present work had as objective to elaborate a flour, from the utilization of the kiwi peel and to characterize how many to the physicochemical and microbiological parameters. For the preparation of the flour were used kiwi peel cv. Hayward in which they were subjected to the drying process at 35 ° C within 72 hours. The obtained flour was analyzed for the following physicochemical parameters: humidity, total solids, water activity, ashes, lipids, proteins, carbohydrates, pH, acidity, vitamin C, chlorophyll a and b, total chlorophyll and total carotenoids; The microbiological parameters evaluated were: total and thermotolerant coliforms, E. coli, mold and yeast, staphylococcus aureus, salmonella spp. The drying process decreased the moisture, water activity of the kiwi peel and can be stored and used for a longer period of time, just as this same process resulted in increased ash, lipid, carbohydrate and chlorophyll contents showing the potential use of this waste. From the results of the microbiological analysis, the kiwi peel flour presented satisfactory results, within the standards established by the current legislation, being considered appropriate for the hygienic-sanitary quality. These results are important because they demonstrate that the processing for flour preparation met the necessary requirements for its future use in the manufacture of new food products.